2012
DOI: 10.1002/glia.22374
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal administration of aTf protects and repairs the neonatal white matter after a cerebral hypoxic–ischemic event

Abstract: Our previous studies showed that the intracerebral injection of apotransferrin (aTf) attenuates white matter damage and accelerates the remyelination process in a neonatal rat model of cerebral hypoxia‐ischemia (HI) injury. However, the intracerebral injection of aTf might not be practical for clinical treatments. Therefore, the development of less invasive techniques capable of delivering aTf to the central nervous system would clearly aid in its effective clinical use. In this work, we have determined whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 57 publications
2
24
0
Order By: Relevance
“…Repeated intranasal delivery of heparin-binding EGF immediately after hypoxic exposure led to reduced OL death, enhanced OL genesis, and improved behavioral recovery in mice 160 . Intranasal administration of human aTf prior to hypoxia-ischemia resulted in less WM injury and an increase in OPC survival and proliferation within the corpus callosum and subventricular zone in mice 161 . Together, these studies provide insights into the dynamic cellular and molecular mechanisms involved in WM injury and recovery imposed by chronic hypoxic exposure and hypoxia-ischemia and offer therapeutic avenues which should be explored in models of CHD-induced WM injury.…”
Section: Animal Models In Chdmentioning
confidence: 92%
“…Repeated intranasal delivery of heparin-binding EGF immediately after hypoxic exposure led to reduced OL death, enhanced OL genesis, and improved behavioral recovery in mice 160 . Intranasal administration of human aTf prior to hypoxia-ischemia resulted in less WM injury and an increase in OPC survival and proliferation within the corpus callosum and subventricular zone in mice 161 . Together, these studies provide insights into the dynamic cellular and molecular mechanisms involved in WM injury and recovery imposed by chronic hypoxic exposure and hypoxia-ischemia and offer therapeutic avenues which should be explored in models of CHD-induced WM injury.…”
Section: Animal Models In Chdmentioning
confidence: 92%
“…Iron deficiency causes hypomyelination and neurological abnormalities, which can be reversed by intracranial injection of apotransferrin (aTf) at early developmental stages (Badaracco et al, 2008). The use of aTf to restore physiological levels of iron transport has been explored in neonatal WMI after HI, as HI increases iron release in WM regions (Guardia Clausi et al, 2012). Intranasal administration of aTf immediately after HI promoted neuroprotection of the neonatal mouse brain by reducing WM damage, astrogliosis, and OL death.…”
Section: Oligodendrocyte Regeneration In the Developing Brainmentioning
confidence: 99%
“…Intranasal delivery of drugs and growth factors has been used for different types of brain disorders and neurological conditions (Dhuria, Hanson et al 2010). A few studies have reported successful interventions in animal models of premature brain injury based on intranasal delivery of factors (Guardia Clausi, Paez et al 2012, Scafidi, Hammond et al 2014). As mentioned above, intranasal delivery of heparin binding-EGF was recently reported to ameliorate rodent preterm WMI (Scafidi, Hammond et al 2014).…”
Section: Key Factors Controlling Delayed Maturation and Recoverymentioning
confidence: 99%